As narrativas que circulam sobre o curso de letras: memórias recontadas por quem deixou o seu lar para estudar - Lutz, Cláudia Raquel (2013)
This research consists of an interpretative analyses of life narratives of three students or newly degreed in Languages in a Federal University of Rio Grande do Sul, who left their homes in order to study. From those analyses, some discourses emerge and produce meanings about the course in question. This study is in line with the field of Cultural Studies by post- structuralism and also post-modernism perspectives, in which the language forms the individuals. These social actors are multifaceted and through their narratives, they are positioned in some discursive network that is crossed by power relations. This hybrid character of identities sets the individuals as a changeable being since they are always susceptible to transformations. Those different sides are permeated by various voices that build those human beings and impose meanings to their lives. Among the issues approached in this research, the teacher's representation is one of the most important as well as historical topics which enable us to understand why the Language course and other degrees in the educational area, in general, are downgraded by the society. This value given to certain courses is not considered natural by the perspective of this study and, for this reason, discourses that pursue to legitimate these thoughts are problematized. The data collection was done by semi structured interviews, individual or in groups, with three women-Language-students. Some concepts are relevant to this research, for instance: identity and difference, representations, signifying practices, the Linguistic Turn and life narratives. Authors such as Hall (1999, 1997), Larrosa (1995), Costa (2000, 2002, 2006), Silva (1999, 2000, 2001) and Veiga-Neto (2000, 2003) guided this study. The research points to some representations of teachers presented in the narratives of the participants and that help us to understand the historical issues that make Language courses to be discredited to the society.